Identifying the accessibility barriers for chronic disease management in health care delivery system amongst the Urban Poor of Kolkata, West Bengal, India - Priyanka Roy; Mainak Bardhan (Journal of Family Medicine and Primary Care, 2025)
Background: Challenges the socioeconomically vulnerable urban population faces in managing chronic diseases are compounded by deficiencies and lacunae in the healthcare delivery system. In the socioeconomic context of chronic disease management (CDM) under the ambit of the healthcare delivery system under National Urban Health Mission (NUHM), there is a dearth of adequate provision of health services and its delivery mechanisms to mitigate the issues. The objective of this research was to identify the barriers that lead to the snowballing of the deficiencies and inadequacies of the healthcare delivery mechanism related to CDM amongst the urban poor of Kolkata. Materials and Methods: The design of this study was a sequential explanatory mixed method using both structured and semistructured tools. The quantitative and qualitative data were collected separately at different time intervals and integrated to establish the interpretation. The study locations were Kalighat, Khidirpur, Mominpur, Ekbalpur, Ultadanga, and Brace Bridge under Kolkata Municipal Corporation, West Bengal. The total number of respondents was 271, which included NUHM programme officers at the state level, service providers at Urban Primary Health Centres (UPHCs), and urban poor population beneficiaries. Results: The accessibility barriers were the location of UPHCs, logistics barriers, quality of care and patients dissatisfaction, out-door timing, lack of medicines, diagnostics facilities, job loss due to repeated health visits, patients’ choice, preference over secondary and tertiary care delivery centres, inadequate information, education and communication, and dysfunctional referral system. Conclusions: There are several accessibility barriers to appropriate healthcare relevant to CDM and a huge implementation gap under NUHM policy.